Surface defect assisted broad spectra emission from CdSe quantum dots for white LED application. (7th February 2018) - Samuel, Boni; Mathew, S; Anand, V R; Correya, Adrine Antony; Nampoori, V P N; Mujeeb, A
Abstract: This paper reports, broadband photoluminescence from CdSe quantum dots (QDs) under the excitation of 403 nm using fluorimeter and 403 nm CW laser excitation. The broad spectrum obtained from the colloidal quantum dots was ranges from 450 nm to 800 nm. The broadness of the spectra was attributed to the merging of band edge and defect driven emissions from the QDs. Six different sizes of particles were prepared via kinetic growth method by using CdO and elemental Se as sources of Cd and Se respectively. The particle sizes were measured from TEM images. The size dependent effect on broad emission was also studied and the defect state emission was found to be predominant in very small QDs. The defect driven emission was also observed to be redshifted, similar to the band edge emission, due to quantum confinement effect. The emission corresponding to different laser power was also studied and a linear relation was obtained. In order to study the colour characteristics of the emission, CIE chromaticity coordinate, CRI and CCT of the prepared samples were measured. It is observed that, these values were tunable by the addition of suitable intensity of blue light from the excitation source to yield white light of various colour temperatures. The broad photoluminescence spectrum of the QDs, were compared with that of a commercially available white LED. It was found that the prepared QDs are good alternatives for the phosphor in phosphor converted white LEDs, to provide good spectral tunability.